Rhizomatic Learning: â€œAsâ€¦ Whenâ€¦ and Ifâ€¦â€ A Strategy for the ASEAN Community in the 21st Century - Lian, Andrew; Pineda, Maria Victoria (Widya Mandala Catholic University Surabaya, 2014)
The article begins with developments in the ASEAN region. In particular, it focuses on demands generated by the goal to build an ASEAN Community characterized by great diversity amongst member countries. The demands created by this diversity are exacerbated by the immense changes taking place in the 21st century, such as unprecedented richness of information and communication systems, unprecedented mobility and the technological empowerment of ordinary people to create or find their own personal solutions in a just in time, just enough and just for me fashion. This leads to the conclusion that learning needs will be vastly different, individual and largely unpredicted and unpredictable. This realisation implies the necessity to develop adaptable, flexible, yet intellectually coherent learning frameworks which will provide the necessary guidance for creating appropriate learning environments. The article proceeds to construct such a framework on the basis of a five-point analysis of how human perception, understanding and knowledge-construction operate. It then develops a learning structure based on the generation of personal learning environments (PLEs) connected to a networked information technology infrastructure which is essentially rhizomatic in nature (i.e. where learners determine the ways that they navigate through information and feedback mechanisms to construct personally-relevant and appropriate knowledge). The article ends with a short scenario to illustrate the workings of this structure and concludes with some remarks about current research in the area in both Asia and Europe